PERAN KEPEMIMPINAN DALAM PENINGKATAN KUALITAS MUTU PENDIDIKAN MELALUI PENGAMBILAN KEBIJAKAN BERBASIS DATA - Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to examine the role of leadership in improving the quality of education through data-driven policy making. The study employs a qualitative approach with a library research design supported by relevant scientific literature. The findings indicate that leadership plays a strategic role in determining effective and targeted educational policies. The use of data in decision-making enables leaders to objectively identify problems, set priorities, and formulate policies that align with actual needs in the field. Furthermore, data-driven leadership contributes to improving organizational performance, strengthening continuous evaluation processes, and fostering a transparent and collaborative organizational culture. However, its implementation still faces several challenges, including limited data literacy, inadequate information systems, and a lack of data-use culture. Therefore, strengthening efforts are needed through capacity building, development of information systems, and the establishment of a data-driven work culture. In conclusion, data-driven leadership is a key factor in achieving sustainable improvement in educational quality. Keywords: Educational leadership, educational quality, data-driven policy, decision making, data-driven decision making